A review of entrepreneurship and circular economy research: state of the art and future directions - Suchek, Nathalia (2022)
The circular economy (CE) emerged as an alternative model to the linear system to foster sustainable development. Entrepreneurship represents a key factor in capturing new circular business opportunities. Research on circular entrepreneurship remains at an early phase and is correspondingly somewhat dispersed. Thus, the research objective here is to bring entrepreneurship into the focus of discussions on CE through a systematic literature review. In the absence of any systematic review on this theme, this work aims to map the relevant research and identify the themes discussed in the literature straddling entrepreneurship and the CE currently dispersed across the existing literature. Based on a sample of 102 articles collected from the Scopus and Web of Science databases, this approach identified four thematic groups: growing circular SMEs, born circular firms and start-ups, social entrepreneurship in CE, and support ecosystem for circular entrepreneurship. A greater emphasis on the study of growing circular SMEs to the detriment of other groups is observed. Also, research in the field is mainly focused on European countries. We then propose a future research agenda and a conceptual model for the entrepreneurial process in CE as a point of departure for further developing and deepening the literature on circular entrepreneurship.